2019
DOI: 10.3389/fpsyt.2019.00454
|View full text |Cite
|
Sign up to set email alerts
|

Female Gaming, Gaming Addiction, and the Role of Women Within Gaming Culture: A Narrative Literature Review

Abstract: Research investigating female gaming has begun to emerge despite gaming being traditionally more popular with males. Research in the 21st century has drawn attention to the role of women in culture, society, and technology, and female gaming is one of the growing phenomena not to have been researched in depth. The aim of the present paper was to review female gaming (i.e., the role of females within video game culture) and identify any associated psychopathological symptomatology. The review adapted the Sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 76 publications
5
79
0
20
Order By: Relevance
“…Prior research has shown that eSports' so-called "core-genres" (such as tactical shooters, fighting games, or sport games) are more strongly favored by men [37]. The eSports scene in terms of community and game design is strongly influenced by men and a male perspective, respectively [37,38]. This may tend to predominantly attract male players and, in this way, lead to a vicious circle.…”
Section: Key Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown that eSports' so-called "core-genres" (such as tactical shooters, fighting games, or sport games) are more strongly favored by men [37]. The eSports scene in terms of community and game design is strongly influenced by men and a male perspective, respectively [37,38]. This may tend to predominantly attract male players and, in this way, lead to a vicious circle.…”
Section: Key Resultsmentioning
confidence: 99%
“…This may tend to predominantly attract male players and, in this way, lead to a vicious circle. Additionally, sexism, offensive language and online harassment are reoccurring problems in some eSports titles [38][39][40][41] that might further deter female players.…”
Section: Key Resultsmentioning
confidence: 99%
“…Additionally, other structural characteristics may also contribute to habitual videogame usage (see Griffiths & Nuyens, 2017 ), such as the inclusion of gambling elements (e.g., loot boxes) in computer games ( Drummond & Sauer, 2018 ; Griffiths, 2018b , 2018c ). Moreover, previous research ( Hartmann & Klimmt, 2006 ; Lopez-Fernandez et al, 2019 ; McLean & Griffiths, 2019 ) also showed that female gamers prefer different game features to male gamers. Consequently, self-control may have different challenges among female and male gamer groups.…”
Section: Introductionmentioning
confidence: 83%
“…More specifically, male gamers play videogames in person or online with friends more frequently than female gamers [129]. Additionally, male gamers look for different things in videogames than female gamers, which are often included in game designs, thereby enhancing male gamers' abilities [130]. Additionally, female gamers face the sexual (mis)representation of female characters in the game, online harassment, and the expectation that they are less skillful players compared to male gamers [131].…”
Section: Plos Onementioning
confidence: 99%